Effect of the season of treatment by urea on the food value of straw on sheep (Sciences & Technologie. C, Biotechnologies, 2007)
The study of the effect of the season of treatment (summer or winter) of straws by urea shows that: -  The content of dry matter and the rate of hemicelluloses of the straw are affected whatever the season of treatment. -  The intake of the straw treated by urea in winter is better than that observed for the straw treated in summer (on average 68.4 g/d/kg P0.75 against 61.8 g/d/kgP0.75) -  The digestibility of the organic matter of the straw treated by urea in winter is slightly lower than that of the straw treated in summer since this one passes from 45.5% for the straw untreated with 49.8 and 54.0% respectively for the straw treated in winter and the straw treated in summer. The digestibility of the total nitrogenized matters is on the other hand definitely higher for the straw treated in winter, that is to say 64.9% against 54.1% for the straw treated in summer. -  The nitrogen selected is established on average with 6.33g for the straw treated in winter against 5.33g for the straw treated in summer. -  Whatever season of treatment; the straw treated by urea largely meets the needs for maintenance of sheep.